2018
DOI: 10.1016/j.biopsych.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

From Traumatic Childhood to Cocaine Abuse: The Critical Function of the Immune System

Abstract: Collectively, our findings demonstrate that sensitization to cocaine in early life-stressed individuals involves brain and peripheral immune responses and that this mechanism is shared between mice and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 58 publications
4
40
0
Order By: Relevance
“…D2 auto-receptor pathways show plasticity and are dynamically regulated by reward circuits and drugs of abuse (Beckstead et al, 2007;Courtney et al, 2012). Here, we found that the VTA DA neurons from the socially defeated mice lost their inhibitory responses to DA, which is consistent with other results reported that social defeat stress reduces the degree of DA-mediated self-inhibition of VTA DA neurons, and also the amplitude of DA-induced outward currents in the VTA (Lo Iacono et al, 2018). We speculate that the coupling between the D2 receptor and Kv7 was altered, or that the D2 receptor was downregulated or desensitized, or mechanisms targeted by microglia after social defeat stress (Ford, 2014;Lo Iacono et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…D2 auto-receptor pathways show plasticity and are dynamically regulated by reward circuits and drugs of abuse (Beckstead et al, 2007;Courtney et al, 2012). Here, we found that the VTA DA neurons from the socially defeated mice lost their inhibitory responses to DA, which is consistent with other results reported that social defeat stress reduces the degree of DA-mediated self-inhibition of VTA DA neurons, and also the amplitude of DA-induced outward currents in the VTA (Lo Iacono et al, 2018). We speculate that the coupling between the D2 receptor and Kv7 was altered, or that the D2 receptor was downregulated or desensitized, or mechanisms targeted by microglia after social defeat stress (Ford, 2014;Lo Iacono et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In adulthood, cell density returned to control levels, but microglia displayed increased soma size and process complexity close to the soma. Interestingly, the microglial cells of stressed mice showed a higher IBA-1 percentage of expression in response to cocaine injection (5 mg/kg) with respect to controls, indicating a possible effect of early social stress on microglial priming [69]. Differently, a paradigm of social instability stress applied during adolescence (isolation and change of cage partner) did not produce effects on counts of microglia in the dentate gyrus (HIP) either early or later after the stress exposure [70].…”
Section: Postnatal Behavioral Stressorsmentioning
confidence: 93%
“…First, many of these studies have focused on one or few target structures for investigation, particularly the HIP. As reviewed by Tan, Yuan, and Tian (2019), microglia show regional heterogeneity in density, morphology, and phenotype, which may underlie differential responsivity to stimuli, including stress and inflammatory conditions [69,169]. This spatial heterogeneity could be important for tuning neuronal/glial functions and neural circuitry, thus contributing to the region-specific effects of ELS on the brain.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of branch points (nodes), processes that intersected the radii, was measured as a function of the distance from the cell soma for each radius. 24,32 Data were collected and stored for statistical analysis. Fifteen cells per animal were randomly selected for a total of 90 cells per group (N = 6 mice/group) and included for analysis.…”
Section: Quantitative Analysis Of Microgliamentioning
confidence: 99%